The Relationship between Sustainable Human Resource Management and Employee Loyalty in Manufacturing Industry in Malaysia - Hussain, Tivyaa; R. Chandrashekar, (Research in Management of Technology and Business, 2025)
This study examines the relationship between Sustainable Human Resource Management (SHRM) practices and employee loyalty in Malaysia’s manufacturing sector. As sustainability becomes a business priority, HRM plays a crucial role in fostering long-term commitment and trust among employees. The research focuses on five key SHRM components: recruitment, training and development, performance management, employee relations, and remuneration. A quantitative survey of 384 employees from manufacturing firms in Selangor revealed a significant positive correlation between SHRM practices and employee loyalty. Sustainable recruitment and performance management emerged as critical factors, while training, remuneration, and employee relations further reinforced employee commitment. These findings highlight the importance of integrating sustainability into HR policies to reduce turnover and enhance workforce engagement. By aligning HR strategies with corporate sustainability goals, organizations can create a more supportive and resilient workforce, ultimately driving long-term business success.